More than tears: associations between exposure to chemical agents used by law enforcement and adverse reproductive health outcomes - Hassan, Asha; Ojanen-Goldsmith, Alison; Hing, Anna K.; Mahoney, Madeline; Traxler, Sarah; Boraas, Christy M. (Frontiers in Epidemiology, 2023)
Despite routine law enforcement use of chemical agents for crowd control, the reproductive health safety profiles of these products are unknown. Moreover, limited evidence has documented a link between such exposures and adverse reproductive health outcomes including abnormal uterine bleeding and potential pregnancy disruption. This cross-sectional study examined reproductive outcomes in adults with uteri exposed to chemical agents used by law enforcement, more commonly known as "tear gas". Participants were recruited through social media in the wake of police violence protests. Of the 1,276 participants included in analysis, 83% reported experiencing at least one of the outcomes of interest, included uterine cramping (69%), early menstrual bleeding (55%), breast tenderness (30%), and delayed menstrual bleeding (21%). Chemical agent exposure was significantly associated with higher odds of an adverse reproductive health outcome, those with 5 days or more of exposure have 2.6 times the odds (CI 1.61, 4.22) of adverse outcomes. and having a perception that one's menstruation may fluctuate according to psychosocial stressors was associated (OR=1.94, CI: 1.36, 2.79) with a higher odds of an adverse reproductive health experience. These findings suggest a potential relationship between exposure to chemical agents and adverse reproductive health outcomes. Given the pervasive use of these chemical agents and their potential for reproductive health harm, further investigation into the safety of these products and their impacts on individual and community health is warranted urgently.